Jamaica : Sixth Review Under the Stand-By Arrangements-Press Release; Staff Report; and Statement by the Executive Direct for Jamaica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Jamaica's Sixth Review Under the Stand-By Arrangement (SBA). All quantitative performance criteria, indicative targets, and the structural benchmark at end-June were met, marking a successful completion of the SBA. Discussions centered on policies to lock-in macroeconomic stability and advance supply-side reforms to promote inclusive growth, including: building institutions and advancing fiscal reforms to safeguard and sustain economic stability and debt reduction; improving monetary operations and policy transmission; and bolstering financial inclusion, access to credit, and formality. Most structural policy commitments are on track, although some key reforms to public sector transformation, the compensation framework for public employees, legislation to establish a fiscal council, and creating a special resolution regime for financial institutions have been delayed due to capacity constraints and the need to build stakeholder support for these reforms. Important gains have been made in the oversight of financial institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet